Applying Hemingway App to Enhance Students' Writing Skill - Muhammad Chairil Imran (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The research mainly discusses the application of Hemingway App to Enhance Students' Writing Skill. The researchers selected the sample from the population by using random sampling technique. The number of the sample was 30 students. This research was a pre-experimental design with one group pretest and posttest. The group was tested after treatment, the test was writing test. The result of data analysis showed that there was a significant difference between the mean scores of pretest and posttest. The mean score of posttest was greater than the mean score of pretest. The mean pre-test of the students was 54.68 while the mean post-test was 82.76. It can be concluded that the application of Hemingway App enhances students' writing Skill. It means that there is a significant difference (H1) of the students' writing Skill before and after treatment by applying Hemingway App.